EFFECT OF PVD COATED TOOLS ON HYPOEUTECTIC ALUMINIUM ALLOY DURING DRY MACHINING PROCESS - Tanaji Burungale1 Ameet Rupnar2 Sandeepraj Salunkhe3 (International Journal of Innovations in Engineering Research and Technology, 2022)
The great challenge of today’s Industries is to process smooth production. Material like Aluminium Alloys machining is a greater challenge for the Aerospace, Automobile due to their peculiar character weight by volume ratio. Silicon in the Al alloy is lesser than 12% is commonly known as Hypoeutectic Al Alloy. Machining is a further challenge for this Hypoeutectic alloy. Dry machining process is an economic and environmental healthy process. In the present study Hypoeutectic Aluminium alloy is machined using PVD coated Diamond like Carbon (DLC), AlCrN and Uncoated Carbide cutting tool. Minitab statistical software is used to produce L27 Array for 3 factor and 3 levels of variables to conduct turning experiment. Average Surface roughnesses are recorded to optimize the cutting parameters for each tool using Taguchi analysis for the dry machining process. AlCrN coated tool machining gives minimum Ra= 0.649 µm at 2000 rpm Speed, 0.02 mm/rev feed rate and 0.25mm depth of cut. The study also shows that coated tools shows appreciable results compared with uncoated tools to achieve optimized surface finish.